New poverty, precariousness and minimum income: reforms for encouraging the employment in the current context - Martínez Virto, Lucía (Cuadernos de Relaciones Laborales, 2019)
The deterioration of working conditions once again intensifies the traditional debate on how to prevent social protection from discouraging return to employment. Labour precariousness is a brake to achieve contributive benefits, and even to overcome situations of poverty. In this scenario, the minimum income benefits, originating from charity, are those that protect many of these situations, due to more flexible access requirements. However, these benefits were neither prepared to deal with this volume of people nor to the complexity of new profiles such as the working poor. That is why these tools are subject to a debate and social attention. How to ensure that their protective vocation does not discourage labour insertion? The text presents some of the main challenges of the system to adapt it to this matter.
Keywords: minimum income benefits; precariousness; working poor; work incentives; jobs transition benefits